A novel approach for benchmarking and assessing the performance of state estimators. (September 2018) - Das, Laya; Kumar, Gaurav; Rengaswamy, Raghunathan; Srinivasan, Babji
Abstract: State estimation is a widely adopted soft sensing technique that incorporates predictions from an accurate model of the process and measurements to provide reliable estimates of unmeasured variables. The reliability of such estimators is threatened by measurement related challenges and model inaccuracies. In this article, a method for benchmarking of state estimation techniques is proposed. This method can be used to quantify the performance and hence reliability of an estimator. The Hurst exponents of a posteriori filtering errors are analyzed to characterize a benchmark (minimum mean squared error) estimator, similar to the minimum variance control benchmark developed for control loops. A distance metric is then used to quantify the extent of deviation of an estimator from the benchmark. The proposed technique is developed for linear systems and extended to non-linear systems with single as well as multiple measurable variables. Simulation studies are carried out with Kalman based as well as Monte Carlo based estimators whose computational details are significantly different. Results reveal that the technique serves as a tool that can quantify the performance and assess the reliability of a state estimator. The strengths and limitations of the proposed technique are discussed with guidelines on applications and deployment of the technique in a real life system. Highlights: State estimation is a widely used soft sensing tool. The performance of an estimator is dependent on modeling accuracy and approximations. A method for benchmarking the performance of estimators along with a measure of performance with respect to the benchmark are proposed. The method is independent of the nature of the system and computational details of the estimator.